Guía Didáctica Digital “Anato Explora” para el aprendizaje de la Biología Humana: Anatomía y Fisiología Humana con los estudiantes de sexto semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Escobar Lemache, Cinthya Dayana (2025)
Currently, problems that lead to demotivation, disinterest, and apathy when studying complicated and theoretical content are caused by the inadequate use of digital teaching tools in the educational process as well as the repeated approaches. Furthermore, "analog tools" are difficult to use. A digital teaching guide is an alternative that allows students to develop attention, memory, and reasoning skills when processing, interpreting, deducing, and retaining information over the long term. Therefore, the objective of this research was to "Propose the "Anato Explora" Digital Teaching Guide to facilitate the learning of Human Biology: Human Anatomy and Physiology with sixth-semester students of the Pedagogy of Experimental Sciences in Chemistry and Biology program." Equally important, the method used was quantitative, non-experimental, descriptive, and bibliographic. A survey of ten closed-ended questions was applied to thirty-five students to collect data related to the subject of study. In conclusion, the use of the "Anato Explora" guide fosters dynamic and systematic learning through active participation, which is important when constructing knowledge, thus facilitating the acquisition of complex theoretical content. Likewise, the importance of these tools, which allow for the renewal of critical thinking and autonomous learning, was highlighted. The use of innovative resources was emphasized because their design, structure, and interactive activities facilitate the educational process.